Collaborative Learning at University: The World Café in Communication Education - Muñoz-Sastre, Daniel; Rodrigo-Martín, Luis; Rodrigo-Martín, Isabel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The study evaluates the impact of the World Café methodology in university teaching, highlighting its capacity to promote active, horizontal and collaborative learning. It analysed qualitative and quantitative responses from participants who positively valued aspects such as active participation, interpersonal interaction and the development of skills such as communication and critical thinking. Despite challenges such as logistics and initial resistance, the World Café proved to be an effective tool to enrich learning. Organisational adjustments and future explorations in various educational contexts are recommended.